(untitled) (Geo-Eco-Marina, 2023)
The description of Cytheridella ilosvayi Daday, 1905 is reviewed and new information on the morphology of the valves is presented. Traits belonging to the areas of the dorsal and antero- and postero-ventral margins of the valves are described for the first time and a novel method to evaluate the degree of inclination of the valve’s dorsal margin is proposed. The data are further used for reviewing the taxonomic validity of the fossil (Neogene) C. danielopoli Purper, 1979, occurring in Western Amazonia. It is documented that the C. danielopoli described by Purper (1979) is closely related to C. ilosvayi. specimens presented by Gross et al. (2013), considered initially as variants of C. danielopoli Purper represent a new taxon, C. martingrossi Danielopol and Piller, n. sp. The information we offer are premises for an extended study we intend to complete on the morphology and systematics of Cytheridella species.